Hollowness of Imagination: Common Sense and Democracy - Ben Kristian Citto Laksana; Lidia Kristi Agustina (Jurnal Ilmiah Hubungan Internasional, 2022)
The transition to democracy in Indonesia has somehow resulted in a majoritarian democracy. By linking the legacy of the New Order regime with the current understanding of democracy, this paper attempts to comprehend and analyze how deeply the common sense of the New Order regime has been rooted in the lives of Indonesian people. The legacy of the New Order regime has been rooted in the personal lives of individuals because the regime implemented its values ​​in the realm of family structures and education systems. To help liberate the minds and souls of Indonesians and be truly democratic, society must be able to become autonomous. A critical pedagogical approach will help to lay bare the common sense and values ​​that have been instilled by the regime, so that people can live autonomously and side by side. Since democracy in Indonesia tends to favor the majority, this study proposes a critical pedagogical approach at every level of society to achieve a power sharing arrangement.